Parent satisfaction with a pediatric practice in Germany: A questionnaire-based study - Luchter Elisabeth; Villalon Gloria; Straeter Alexandra; Weissenstein Anne; Bittmann Stefan (BMC, 2011)
Abstract Background Parental satisfaction with a pediatric day center is essential for the medical treatment of children, since it is closely related to compliance. In order to ascertain factors which predict parental satisfaction as well as to discover possible weak points, we developed a questionnaire. Methods 127 parents visiting the pediatric day center from October to November 2010 were asked to respond to a questionnaire. The survey was given to them directly by the doctor after their visit and it provided the opportunity to determine subjective and soft factors in quality management, which is essential for a pediatric practice. The questionnaire consisted of 27 items divided into three scales. The scales were as follows: satisfaction concerning the infrastructure and organization, satisfaction concerning the communicative and empathic competence of the doctor as well as the other staff, and finally the results and the overall impression. Moreover, the survey asked the respondents for their comments on the pediatric day center and sociodemographic data were queried. Results A total of 67 parents (52,7%) responded to the survey. The mean parental satisfaction concerning infrastructure and organization achieved 3,61 (scale 1-very unsatisfied-through 4-very satisfied). The mean satisfaction with the expertise of the doctor and the staff was 3,56 and the overall satisfaction was 3,65. Ninety-one percent of the parents would visit the pediatric practice again and 84,2% would definitely recommend the practice to others. Conclusion Surveys on parental satisfaction are essential for the success of a pediatric day center. Apart from the doctors abilities to interact with the parents, other factors, such as a short waiting period, a friendly and helpful staff, as well as appealing premises are essential for a high overall level of satisfaction.